Bearing Capacity of Concrete Filled Steel Tube Circular Arch under the Six-Point Uniformly Distributed Loading and Its Engineering Application. (13th December 2021) - Liu, Keming; Sun, Xizhen
Abstract : The influence of rise-span ratio on the bearing performance of concrete filled steel tube (CFST) circular arch was studied in this paper, three groups of CFST circular arch specimens with different rise-span ratios (0.154, 0.207, and 0.26) were selected, the six-point uniformly distributed loading was performed, and bearing performance experiments on CFST circular arch specimens with fixed ends were carried out. In this study, the ultimate bearing capacity and deformation failure characteristics of CFST circular arch specimens were obtained. The comparative analysis shows that the deformation evolution of CFST circular arch specimens has experienced compaction stage, elastic stage, elastic-plastic stage, and plastic stage. In the elastic-plastic and plastic deformation stages, the circular arch shows good ductility and bearing capacity. The bearing capacity of the circular arch is significantly affected by the rise-span ratio. Compared with circular arch specimens with a rise-span ratio of 0.154, the yield load of specimens with a rise-span ratio of 0.207 and 0.26 is increased by 50.8% and 61.5%, and the ultimate bearing capacity is increased by 42.7% and 68.3%, respectively. The larger the rise-span ratio, the greater the yield load and ultimate bearing capacity of the specimen and the stronger the deformation resistance of circular arch. The numerical simulation on the bending resistance process of circular arch was performed by ABAQUS to present the compression failure process of steel tube and core concrete. The simulation results are in good agreement with the experimental results. The experimental and simulation results show that the circular arch first yields at the inner side of the arch foot, and the curvature of different positions of the specimen is no longer consistent. When the ultimate bearing capacity is reached, the steel pipe at the arch foot obviously heaves, and the hooping effect of the steel pipe on the concrete is invalid. Based on the above research results, a closed composite support scheme of "bolt mesh shotcrete + vertical elliptical CFST support + steel fiber concrete shotcrete layer + reinforced anchor cable" was proposed for the extremely soft rock roadway and successfully applied in the Qingshuiying coal mine.